2015
DOI: 10.1002/path.4601
|View full text |Cite
|
Sign up to set email alerts
|

A candidate gastric stem/progenitor cell marker revealed by genome‐wide analysis

Abstract: The authors further demonstrated that up-regulation of E2F1 and ASPM is associated with gastric cancers. This study provides novel candidates for future lineage-tracing experiments that will lead to the ultimate discovery of bona fide gastric stem cell markers. Additionally, the E2F1-ASPM axis may represent a new mechanism for gastric carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…So we named this group as the ASPM + urothelial cells. Genome‐wide analysis has suggested ASPM as a possible gastric stem/progenitor cell marker 26,27 . In the UTI model we established, we found that ASPM + urothelial cells were significantly increased after acute injury, suggesting that ASPM + urothelial cells are involved in the bladder urothelial regeneration.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…So we named this group as the ASPM + urothelial cells. Genome‐wide analysis has suggested ASPM as a possible gastric stem/progenitor cell marker 26,27 . In the UTI model we established, we found that ASPM + urothelial cells were significantly increased after acute injury, suggesting that ASPM + urothelial cells are involved in the bladder urothelial regeneration.…”
Section: Discussionmentioning
confidence: 74%
“…So we named this group as the ASPM + urothelial cells. Genome‐wide analysis has suggested ASPM as a possible stem/progenitor cell marker 26,27 . Immunofluorescence results showed that few ASPM + cell was found in healthy mouse urothelium (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BUB1 co-operates with BUB1B in phosphorylation of mitotic checkpoint complex members and activating the spindle checkpoint [15], while ASPM regulates spindle organization and rotation [16]. BUB1 and ASPM functions appear to be essential for asymmetrically dividing CSC and thus are appealing as targets for selective CSC elimination [1618]. Our analysis performed on hundreds of public cancer datasets (https://www.oncomine.org, http://biit.cs.ut.ee/mem) demonstrated that BUB1 and ASPM are overexpressed in a great variety of solid cancers within a highly conserved and substantial gene signature (>500 genes, p < E–70) (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…We read with great interest the article by Vange et al [1] in the December 2015 issue of the Journal of Pathology, as well as the subsequent commentary by Zhu et al in the January 2016 issue [2]. Vange et al identified a novel possible oxyntic stem/progenitor cell marker ASPM [Asp (abnormal spindle) homologue, microcephaly-associated (Drosophila)] by genome-wide expression analysis of the microdissected isthmus zone, where the majority of stem/progenitor cells are believed to reside.…”
mentioning
confidence: 96%